Influência dos acessos endodônticos ultraconservadores na eficácia do tratamento endodôntico e na resistência à fratura de pré-molares superiores - Silva, Adilson Alves da (2019)
Aim To evaluate the influence of ultraconservative endodontic cavities (UECs) on root canal detection, instrumentation efficacy and fracture resistance assessed in biradicular maxillary premolars. Traditional endodontic cavities (TECs) were used as reference for comparison. Methodology Twenty extracted intact biradicular maxillary premolars were scanned using micro-computed tomographic imaging, pair-matched based on similar anatomic features of the canals, and assigned to the UEC or TEC group (n = 10/group). Then, teeth were mounted on mannequin heads and accessed accordingly. Root canal detection was performed under an operating microscope and ultrasonic troughing. After root canal preparation with Reciproc Blue R25 instruments, the specimens were scanned again. Non-instrumented canal area and accumulation of hard tissue debris were analyzed. After root canal filling and cavity restoration, the total time required to perform endodontic treatment was recorded, specimens were scanned again and after the specimens were loaded to fracture in a universal testing machine. The maximum load at fracture and fracture pattern (restorable or unrestorable) were recorded. Data were statistically analyzed using Shapiro-Wilk and Student´s t test with a significance level of 5%. Results All root canal were localized for both access modalities. The percentage of non-instrumented canal areas did not differ significantly between UEC and TEC groups (P > 0.05). However, UEC group was associated with higher percentage of accumulated hard tissue debris after preparation when compared to TEC group (P < 0.05). Time required to perform root canal treatment was higher in the UEC group when compared to the TEC group (P < 0.05). No differences was observed in root canal filling voids (P<0.05), however UEC present higher unremoved filling material at pulp chamber when compared to TEC (P<0.05). There was no difference regarding the mean load at fracture among the UEC and TEC groups (P > 0.05). Unrestorable fractures were observed in all specimens of both groups. Conclusion The current results did not show benefits associated with UECs. This access modality in biradicular maxillary premolars resulted in higher percentage of accumulated hard tissue debris after preparation, required higher time to perform root canal treatment and worse cleaning of pulp chamber. UECs did not increase the fracture strength of endodontically treated teeth.